Single and double layered microencapsulation of probiotics by spray drying and spray chilling - Arslan-Tontul, Sultan; Erbas, Mustafa (Elsevier Science Bv, 2017)
In this study Saccharomyces boulardii, Lactobacillus acidophilus and Bifidobacterium bifidum were micro-encapsulated using spray drying and spray chilling techniques as single and double layered. For this purpose, as wall material, 10% gum Arabic and beta-cyclodextrin (9:1) were used in spray drying experiment and hydrogenated palm oil was used in spray chilling experiment. According to the results, S. boulardii, L. acidophilus and B. bifidum counts were detected high in single layered microcapsule produced by spray chilling (P) as 8.21, 8.10 and 8.25 log cfu/g, respectively. Double layered microencapsulation improved heat and gastric resistance of L. acidophilus. However, spray dried microcapsules had more protective effect in simulated intestinal system and heat tolerance test. Microencapsulation of L. acidophilus and B. bifidum enhanced high survivability in simulated gastric and intestinal conditions. Moreover, micro encapsulated probiotic microorganisms could survive even at 80 degrees C while free probiotic microorganisms were detected only at 50 degrees C and 30 min holding time. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Saccharomyces boulardii; Lactobacillus acidophilus; Bifidobacterium bifidum; Spray drying; Spray chilling